A Framework To Develop Tools & Techniques Requirements Methodology For Implementing Lean Manufacturing - Perumal, Puvanasvaran A. (2011)
Increased global competition and customer demands that are looking for better quality product with less cost seem to force companies into implementing lean tools and techniques in their production line. This can lead them to keep or strengthen their competitive position by eliminating the waste of non value added activities and producing value to product that meet customer requirements without affecting the actual quality of the product produce. Example can be found in the automotive industry, electronic industry, aerospace industry, but also the service industry. The deployment of tools and techniques of lean manufacturing became important factor in implementing LM in manufacturing industry. This tools and techniques must be deploying properly so it can bring continuous improvement and sustainability in manufacturing perspective. This PhD proposal aspires to research the main question of how to determine the appropriate tools and techniques requirement methodology for an organization to implement and what are the tools and techniques that need to be deployed to achieve successful implementation. The literature review concerning this area of research has established that there were gaps in the knowledge that required further research. These research gaps with research scope are presented in detail in this paper. The overall specifications of the proposed methodology are also discussed.